The Compliance Status of Chemical Management among Industries in Malaysia: The USECHH after 20 years (Journal of Energy and Safety Technology (JEST), 2022)
Chemical management plays an important role in the protection of human health and environment. Malaysia through the Department of Occupational Safety and Health (DOSH) developed chemical related legislations under the Occupational Safety and Health Act (OSHA) 1994 upon tripartite and stakeholder consultation. Effective law enforcement by DOSH is important to ensure compliance to occupational health legislations in order to meet the objectives of OSHA 1994. This paper presents the status of chemical management compliance in Malaysia pertaining to compliance to the Occupational Safety and Health (Use and Standards of Exposure of Chemicals Hazardous to Health) (USECHH) Regulations 2000 among the industries in various economic sectors twenty years after its inception. This paper proposes four steps for investigating the compliance status. The four steps are overview of chemical legislations, enforcement strategies, data analysis and recommendations. There was a total of 9712 workplaces inspected by DOSH officers during the enforcement activities. About 54% workplaces received satisfactory grades while 46% were non satisfactory. USECHH operations for the last five years (2016-2020) revealed that 70% of the total workplaces inspected received satisfactory compliance while another 30% potrayed otherwise. These positive results show significant improvement in the status of compliance of chemical management as compared to the beginning of its introduction in year 2000 where majority of the grades are unsatisfactory. Analysis of each elements found that the worst compliance comes from elements such as medical surveillance, health surveillance, exposure monitoring and chemical health risk assessment The research also prescribes strategies and methods taken by DOSH Malaysia in ensuring chemical management compliance at the workplace. This paper shows an insight of chemical management in Malaysia briefly and provides suggestions and recommendations, measures and outcomes of enforcement. Future measures to be taken by DOSH is also suggested to boost compliance.
Keywords: Keywords: USECHH compliance, self-assessment, checklist, enforcement, punitive actions, chemical management, MyKKP.